Therapy with monoclonal antibodies. An in vivo model for the assessment of therapeutic potential. - Isaacs, J; Clark, MR; Greenwood, J; Waldmann, H (1992)
A set of rat-human and rat-rat chimeric mAb has been created, all possessing V regions identical in their specificity for the mouse CD8 Ag. In vitro all antibodies were able to block cell-mediated lysis but varied greatly in their capacity to utilize rabbit complement. We examined the ability of these chimeric antibodies to deplete in vivo and established a clear hierarchy. Of the human IgG subclasses, only IgG1, 2, and 3 could fix complement in vitro, yet all (IgG1-4) were remarkably potent at depleting CD8+ PBL in vivo. In contrast, human IgA2 and IgE were ineffective at clearing CD8+ PBL. The vector system used to create these antibodies together with the small doses of antibodies required to deplete in vivo make this a simple and rapid system for testing the effects of different antibody isotypes and mutants. We have shown that a mutant of human IgG1, which is incapable of fixing complement, depletes perfectly well in vivo, whereas an aglycosyl IgG1 mutant is rendered inactive. Our model provides a unique opportunity to study effector functions and motifs that are used by mAb in vivo and will help in the design of improved antibodies for human therapy.